An Investigation of the Influence of a Nonstatistical Decision Aid on Auditor Sample Size Decisions - Kachelmeier, Steven J.; Messier, William F. (The Accounting Review, 1990)
[A between-subjects experiment was used to examine the effects of a decision aid in the AICPA's Audit Sampling Audit Guide on the magnitude and variability of auditor sample size judgments. Audit seniors were given background case information for a hypothetical audit task and were randomly assigned to one of three experimental groups: (1) an intuitive judgment group, (2) a decision aid group who calculated sample sizes using the AICPA Guide formula, or (3) a group who provided only the formula parameters from which the researchers later computed implied sample sizes. It was hypothesized that the sample sizes of group 2 would be larger than those of group 1 (due to insensitivity to power considerations), and that the implied sample sizes for group 3 would exceed those of group 2 (due to a tendency for auditors to "work backwards" toward an intuitive sample size). Both of these hypotheses were supported by the data. However, a test for differences in variability indicated that the decision aid led to a greater degree of inconsistency in sample size judgments. Results were consistent over two levels of internal control.]